An investigation into English intonation patterns performed by students in grades 9 at Trung Vuong Lower Secondary School in Danang City - Phạm Lâm Nam Phương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to examine how students in Grade 9 at Trung Vuong Lower Secondary School in Danang City experience English intonation patterns in order to provide practical knowledge to the teaching and learning concerning the enhancement of pronunciation of the English intonation patterns.